An Analytical Study of the Harmonic Accompaniment Patterns According to Carl Orff - Odeh, Tariq William (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to investigate the harmonic accompaniment patterns and forms of musical composition according to Carl Orff's approach used in music education. Methods: The study adopted the descriptive approach (content analysis) based on theory analysis and interpretation in a way that ensures understanding and proposals for its employment by collecting study data using sources, references, and illustrative examples. The study sample consisted of the musical models of the harmonic accompaniment patterns used in Carl Orff’s methodology which was chosen intentionally. Results: The study found that a variety of harmonic companion patterns is used, such as: borden, broken borden, moving chord borden, level borden, crossover borden, drone, and ostinato. The results of the study also showed that the harmonic accompaniment patterns used in Carl Orff’s method represent one of the forms of musical composition called homophonic texture. Conclusions: The study recommends the need to include harmonic accompaniment patterns as synchronization with playing melodic percussion, in addition to the diversification in the use of Orphic harmonic accompaniment patterns, as it represents the homophonic fabric and establishes its understanding and assimilation.